Pengaruh Permainan Ular Tangga Terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun di TK Bintang Pertiwi, Batam – Kepulauan Riau - Helen F Sinambela; Nuryanah Nuryanah; Hariyanti Hariyanti; Widaningsih Widaningsih (Jurnal Pendidikan Tuntas, 2023)
Playing for children is a necessity like food, of course games are needed that lead children to achieve something that is useful for them in the future. Educational games are consciously designed to provide developmental benefits, but are they beneficial for children's cognitive development? This research will of course look at how children's cognitive development occurs by using the educational game Snakes and Ladders. This research was carried out in two cycles and each cycle held two meetings. This research was carried out at Bintang Pertiwi Kindergarten, Batam with research subjects being Group B aged 5-6 years, totaling 28 people. Data collection in this research used observation and documentation techniques. As many as 72% of children are in the BSH category after following a series of cycles, 17% of children are in the BSB category and only 11% are still in the MB category. Positive spike values were achieved by the subject from pre-cycle to cycle II, a progressive and consistent increase. During these cycles, it was concluded that the educational game snakes and ladders could stimulate the cognitive development of children aged 5-6 years at the Bintang Pertiwi Kindergarten Batam - Riau Islands. The implication of this research is that educational games really help the learning process and also the child's development process, especially cognitive development. So, it is hoped that PAUD teachers will be more creative in developing media to optimize the cognitive development of early childhood. Keywords: Cognitive, Educational Game, Snakes and ladders Games